Integrating Horticultural Techniques for the Propagation of Ethnomedicinal Pteridophytes in the Himalayan Region - Maneesha Singh (International Journal of Trends in Horticulture, 2024)
The Doon Valley, including the regions of Dehradun, Mussoorie, and Chakrata in Uttarakhand, India, is rich in ecological and medicinal plant diversity. This study focuses on the geographical distribution, habitats, and medicinal applications of 28 pteridophyte species found in these regions. Detailed field observations and data collection from various scientific journals, databases, and publications have contributed to understanding the traditional and pharmacological uses of these plants. The results show that these pteridophytes have anti-inflammatory, antioxidant, antibacterial, antidiabetic, and wound-healing capabilities. For instance, Adiantum capillus-veneris exhibits antidiabetic and antifungal properties, while Dryopteris cocheleata shows promise as an antimicrobial agent and blood purifier. Such insights highlight the potential of these plants for developing novel treatments in ethnomedicine. This research not only contributes to biodiversity documentation but also underscores the need for conservation and sustainable use of these medicinal plants in the Himalayan regions.
Keywords: Doon valley; Himalayas; Therapeutic Applications; chakrata; ethnomedicine; medicinal pteridophytes; mussoorie; pharmacological properties; plant biodiversity; traditional medicine